2017
DOI: 10.1371/journal.pone.0169974
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Epileptic Drug Combination Efficacy in an In Vitro Seizure Model – Phenytoin and Valproate, Lamotrigine and Valproate

Abstract: In this study, we investigated the relative efficacy of different classes of commonly used anti-epileptic drugs (AEDs) with different mechanisms of action, individually and in combination, to suppress epileptiform discharges in an in vitro model. Extracellular field potential were recorded in 450 μm thick transverse hippocampal slices prepared from juvenile Wistar rats, in which “epileptiform discharges” (ED’s) were produced with a high-K+ (8.5 mM) bicarbonate-buffered saline solution. Single and dual recordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 55 publications
2
10
0
2
Order By: Relevance
“…In our approach using a modified submerged chamber, we mostly observed burst activity (spike and burst activity) described before as interictal-like (Remy et al, 2003; Gabriel et al, 2004; Sandow et al, 2015; Reyes-Garcia et al, 2018) and standing in contrast to ictal discharges lasting >10 s. Brückner and Heinemann (2000) suggested that AEDs applied in brain slices (of non-epileptic animals) rather inhibit ictal but not interictal activity. Other animal studies in vitro , however, demonstrated a robust decrease in interictal activity in the hippocampus upon AED application (Fueta and Avoli, 1992; Holtkamp et al, 2017; Taing et al, 2017), which was comparable to our results with LAC and DMEA. We show that burst activity was sensitive to the approved antiepileptic LAC, indicating that our experimental setting is capable of validating and possibly predicting antiepileptic efficacy for drug development.…”
Section: Discussionsupporting
confidence: 91%
“…In our approach using a modified submerged chamber, we mostly observed burst activity (spike and burst activity) described before as interictal-like (Remy et al, 2003; Gabriel et al, 2004; Sandow et al, 2015; Reyes-Garcia et al, 2018) and standing in contrast to ictal discharges lasting >10 s. Brückner and Heinemann (2000) suggested that AEDs applied in brain slices (of non-epileptic animals) rather inhibit ictal but not interictal activity. Other animal studies in vitro , however, demonstrated a robust decrease in interictal activity in the hippocampus upon AED application (Fueta and Avoli, 1992; Holtkamp et al, 2017; Taing et al, 2017), which was comparable to our results with LAC and DMEA. We show that burst activity was sensitive to the approved antiepileptic LAC, indicating that our experimental setting is capable of validating and possibly predicting antiepileptic efficacy for drug development.…”
Section: Discussionsupporting
confidence: 91%
“…In our hospital, The regimen of LTG + VPA is the most common treatment, Taing et al [29] also pointed out that a combination of LTG and VPA was considered particularly efficacious clinically showed a supra-additive suppression of ED’s, it would be the most common treatment. Gidal et al [30] reported that VPA inhibited the clearance of LTG at a low dose (125 mg/d) and a very low concentration (6.5 μg/mL).…”
Section: Discussionmentioning
confidence: 99%
“…ASD is selected based on the basic principles of epilepsy, and on sex, fertility, age, body weight, drug interactions, and comorbidities. Pharmacological synergistic effects generated by the combination of valproic acid (VPA) and lamotrigine, or the addition of subsequent drugs has a small likelihood of inducing remission [37][38][39][40]. Early surgery in patients with DRE increases the likelihood of post-surgery remission [41].…”
Section: The Problem Of Drug Resistant Epilepsy: Etiology and Current Methods For Overcoming Itmentioning
confidence: 99%